Investigation into the Effectiveness of Combining Transcranial Direct Current Stimulation and Transcutaneous Electrical Nerve Stimulation as Treatment Options for Poststroke Shoulder Pain by Utilizing Functional Near-Infrared Spectroscopy - Li Y; Yan ZP; Zhang NN; Ni J; Wang ZY (Dove Medical Press, 2023)
Yu Li,1 Zhi-Peng Yan,1 Nan-Nan Zhang,1 Jun Ni,1,2 Zhi-Yong Wang1 1Department of Rehabilitation Medicine, National Regional Medical Center, Binhai Campus of the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350212, People's Republic of China; 2Department of Rehabilitation Medicine, the First Affiliated Hospital, Fujian Medical University, Fuzhou, 350005, People's Republic of ChinaCorrespondence: Zhi-Yong Wang, Department of Rehabilitation Medicine, National Regional Medical Center, Binhai Campus of the First Affiliated Hospital of Fujian Medical University, 999 Huashan Road, Fuzhou, 350212, People's Republic of China, Tel +86-13635298857, Email fjykdxwzy@163.comObjective: The aim of this study is to explore the therapeutic effects of transcranial direct current stimulation (tDCS) and transcutaneous electrical nerve stimulation (TENS) on post stroke shoulder pain (PSSP).Methods: We enrolled 13 individuals in this study who underwent three different treatments in a random sequence: active tDCS+active TENS, active tDCS+sham TENS, and sham tDCS+active TENS. Each treatment was administered once, with a 3-day washout period between interventions. A blinded rater assessed the visual analog scale (VAS) scores, fNIRS readings, and sensory and pain tolerance thresholds of the participants before and after the stimulation.Results: All three treatment methods can significantly alleviate PSSP (p< 0.05). Compared with using tDCS alone, tDCS+TENS can significantly improve pain, with a statistically significant difference (p< 0.05). In the 2KHz PTT task, the three treatment methods showed significant differences (p< 0.05) in the mean oxygenated hemoglobin (HbO) levels in the false premotor cortex (PMC)/auxiliary motor area (SMA) before and after intervention.Conclusion: The combination of tDCS+TENS can increase the pain-relieving impact on PSSP when compared to using tDCS alone. TENS may contribute an additional effect on the inhibitory systems influenced by tDCS that help reduce pain.Clinical Registration Number: Registration website: https://www.chictr.org.cn. Registration date: 2022-02-25. Registration number: ChiCTR2200056970.Keywords: functional near-infrared spectroscopy, pain tolerance threshold, post-stroke shoulder pain, transcranial direct current stimulation, transcutaneous electrical nerve stimulation